Taxonomic review of the Grammia nevadensis species group (Lepidoptera: Arctiidae) with descriptions of` two new species - Ferguson, Douglas C.; Schmidt, B. Christian (Zootaxa, 2007)
Grammia nevadensis (Grote & Robinson) is revised to consist of four subspecies: nevadensis, geneura (Strecker) revised status, gibsoni (McDunnough) revised status and superba (Stretch). Grammia behrii (Stretch) revised status is raised from synonymy with G. nevadensis and re-described, and a neotype is designated. Two new species of Grammia in the nevadensis species group are described from the western United States: Grammia eureka new species is described from three specimens collected nearly a century ago in central Utah and one specimen ostensibly from southern Idaho. Grammia bowmani new species is a locally common species occurring in southwestern Colorado and southeastern Utah. The adults and male genitalic structures of G. nevadensis, G. behrii, G. incorrupta, G. williamsii, G. eureka and G. bowmani are illustrated.